1998
DOI: 10.1016/s0006-3495(98)77502-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Solvent around Biomolecular Solutes: A Molecular Dynamics Simulation Study

Abstract: Effects of the macromolecular solute on the translational mobility of surrounding solvent water, and Na+ and Cl- ions are investigated by molecular dynamics (MD) simulation. Using MD trajectories of myoglobin and d(C5T5) . d(G5A5) DNA decamer of high quality and length, we determine the average diffusion coefficients for all solvent species as a function of distance from the closest solute atom. We examine solvent mobility in the directions parallel and perpendicular to the solute surface and in proximity to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
188
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 152 publications
(207 citation statements)
references
References 44 publications
18
188
1
Order By: Relevance
“…Whereas the existence of hydration layers of over 10 Å has not been reported experimentally, such large layers containing water dynamically distinct from water in the bulk have been found in earlier molecular dynamics simulations (22,23). In addition to the dipole autocorrelation function and terahertz spectra discussed above, a hydration layer corresponding to water dynamics distinct from bulk water can be quantified by the hydrogen bond correlation function, C(t), which yields the probability that a hydrogen bond that exists between two water molecules at a given time, t ϭ 0, is present at a later time, t, regardless whether the bond has been broken between 0 and t. MD simulations of solvated globular * 6-85 at 27°C reveals that the hydrogen bond correlation function for water molecules in 2-Å-thick layers of water up to 10 Å from globular 6-85 * is distinct from the hydrogen bond correlation function computed for bulk water (23), as we show in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Whereas the existence of hydration layers of over 10 Å has not been reported experimentally, such large layers containing water dynamically distinct from water in the bulk have been found in earlier molecular dynamics simulations (22,23). In addition to the dipole autocorrelation function and terahertz spectra discussed above, a hydration layer corresponding to water dynamics distinct from bulk water can be quantified by the hydrogen bond correlation function, C(t), which yields the probability that a hydrogen bond that exists between two water molecules at a given time, t ϭ 0, is present at a later time, t, regardless whether the bond has been broken between 0 and t. MD simulations of solvated globular * 6-85 at 27°C reveals that the hydrogen bond correlation function for water molecules in 2-Å-thick layers of water up to 10 Å from globular 6-85 * is distinct from the hydrogen bond correlation function computed for bulk water (23), as we show in Fig.…”
Section: Discussionmentioning
confidence: 81%
“…The nature of this shell ''layer'' has been the focus of numerous studies both theoretically and experimentally (see refs. [5][6][7][8][9][10][11][12]), yet there is no generalized picture of the dynamics at the local molecular level.…”
mentioning
confidence: 99%
“…X-ray crystallography, neutron diffraction, and molecular dynamics studies have shown (5)(6)(7)(8)(9)(10) that at protein surfaces, water molecules are site-selective and can be restricted in their motion, even existing in the form of clusters in some cases. For example, neutron diffraction experiments (9) followed by molecular dynamics simulations on carboxymyoglobin (10) revealed that among the 89 water molecules associated with the protein, 4 remain bound during the entire length of the molecular dynamics simulation (50 ps), whereas the rest undergo continuous exchange between bound and free states on a variety of time scales.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By considering water molecules in a finite volume element around biomolecules, numerous attempts have been made to calculate solvent diffusion in the hydration layer of proteins/DNA as a function of distance to the surface. 10,[14][15][16] For viscosity as opposed to diffusion, the stress-stress autocorrelation is often used to calculate the viscosity of the bulk fluid from equilibrium molecular dynamics simulations. 17,18 To access the local viscosity of inhomogeneous fluid, such as fluid confined in nanopores or near imposing walls, nonequilibrium molecular dynamics ͑NEMD͒ has been utilized to simulate fluid under sheer flow.…”
Section: Introductionmentioning
confidence: 99%